Decaying woodrat (Neotoma spp.) middens increase soil resources and accelerate decomposition of contemporary litter. (December 2019) - Campos, Herman; Boeing, Wiebke J.; Throop, Heather L.
Abstract: Ecosystem engineers can have broad-reaching impacts when they alter biogeochemical pools and processes, thus affecting resource availability. In the Chihuahuan Desert, woodrats ( Neotoma spp.) build stick nests on the soil surface within Yucca baccata patches. We assessed the impacts of these middens on the underlying soil pools. We also assessed midden impacts on litter decomposition because decomposition exerts control over soil biogeochemical pools. We specifically focused on midden activity state, selecting Yucca patches with no midden, an active midden, or a decayed midden. Soil were analyzed for organic carbon, total nitrogen, and available nitrogen. To probe a mechanistic driver of soil biogeochemical pools, we measured litter mass loss of mesquite leaflets ( Proposis glandulosa ) and poplar wood ( Populus spp.). Soil organic carbon, total nitrogen, available nitrogen and litter decay were all enhanced in decayed midden patches. These results support observations from other species in which the environmental modifications caused by ecosystem engineers persist beyond the life of the engineer. However, in this case the impacts of ecosystem engineers on biogeochemical pools and processes were greater for engineered structures that were not being maintained than for actively maintained structures. Woodrats have long-term impacts on spatial distribution of soil resources through their persistent middens. Highlights: Woodrats build stick nests that persist beyond the lifespan of individual animals. Litter decomposition and soil chemistry are affected by middens. Decaying middens have greater impact on than active middens on soil biogeochemistry. Impacts of woodrats persist beyond the lifetime of these ecosystem engineers.